Female Friendly, Patriarchy, and the Adoption of Arabic Pronouns: Linguistic Analysis of Family Law Verses in the Al-Qur’an - Sultan, Muslihin; Alimin, Alimin; Muttaqin, Ahmad; Hanafi , Syawaluddin; Furqany, Syahril (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
This study examines the use of patriarchal language in the verses of family law in the Quran, which, despite their masculine structure, contain messages that favor female. The study employed a multi-method design that combined critical content analysis with linguistic (lughawī), gender, and Islamic law approaches. In Islamic studies, multi-methods can be called interdisciplinary and multidisciplinary approaches. The data were based on literature studies and in-depth interviews. This study concludes that from a linguistic perspective, the use of ḍamīr in the Quran is an emancipatory strategy, not to perpetuate patriarchal domination. By addressing men who have historically held social and cultural authority, the Qur’an educates them to be aware of injustice and act as agents of change, while encouraging female to recognize and fight for their rights. From a gender perspective, two main characteristics were found: first, the dominant use of male pronouns (ḍamīr muzakkar), which position men as the primary interlocutors, and second, the existence of several privileges attributed to men. Furthermore, this research offers important implications for Arabic language learning pedagogy. Teaching Qur’anic verses needs to be based on a contextual and gender-sensitive approach so that students not only master the linguistic aspects but also understand the socio-cultural dimensions inherent in the text. Communicative and discourse-based methods are recommended to encourage students to analyze lexical choices, metaphors, and pragmatic functions of Arabic that can both reinforce and challenge patriarchal traditions. This approach not only enhances linguistic competence and critical literacy but also equips students with an awareness of justice and equality from the perspective of Islamic family law. Thus, Arabic language learning serves as a medium for social transformation while strengthening moral awareness.